2008
DOI: 10.2217/17520363.2.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Improving Colorectal Cancer Management: The Potential of Proteomics

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. Successful treatment is heavily dependent on tumor stage at the time of detection, but unfortunately CRC is often only detected in advanced stages. New biomarkers in the form of genes or proteins that can be used for diagnosis, prognostication, follow-up, and treatment selection and monitoring could be of great benefit for the management of CRC. Furthermore, proteins could prove valuable new targets for therapy. Therefore, clinical proteomics h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…Although previous studies employing 2D-DIGE analysis of CRC tissues have documented a number of proteins that are either up- or down-regulated in tumour verses normal mucosa [15], the extent to which protein expression profile differences can be detected by direct MALDI-TOF analysis in CRC was not previously known. Analysis of complex protein mixtures by MALDI-TOF MS is inherently limited by the resolution afforded by this type of instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies employing 2D-DIGE analysis of CRC tissues have documented a number of proteins that are either up- or down-regulated in tumour verses normal mucosa [15], the extent to which protein expression profile differences can be detected by direct MALDI-TOF analysis in CRC was not previously known. Analysis of complex protein mixtures by MALDI-TOF MS is inherently limited by the resolution afforded by this type of instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gene expression profiling studies of both mRNA [13] and microRNA [14] have revealed tumour-associated gene expression signatures that form the basis for a molecular classification of disease sub-types that define disease course and treatment response (reviewed in [8]). These studies on gene mutations and RNA expression have been paralleled by analysis of the tumour cell proteome, most commonly employing the technique of two-dimensional difference gel electrophoresis (2D-DIGE) to identify proteins that are differentially expressed in tumour verses normal mucosa tissue (reviewed in [15]). An expanding list of candidate prognostic markers have emerged from these studies including for example, cathepsin D, S100A4 and APAF-1 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analysis of colorectal cancer (CRC) pointed at the HSP60 gene as one of the best indicators for diagnosis [71] and proteomic studies have corroborated this finding [72] giving it diagnostic and prognostic value. Similarly, HSP60 has also been found to be linked to Crohn's disease and ulcerative colitis [73], two conditions with a high risk for CRC development, probably having a pro-inflammatory role in the remodelling of the colonic mucosa via a TLR4-ERK-dependent mechanism [74].…”
Section: Hsp60mentioning
confidence: 99%
“…By using matrix-assisted laser desorption-ionisation time of-flight-mass spectrometry (MALDI-TOF MS) or surface-enhanced laser desorption-ionisation time-of-flight mass spectrometry (SELDI-TOF MS), peptide fragments representing diagnostic molecular signatures from several types of cancer have been identified in blood sera/plasma that discriminate cancer patients from normal individuals [ 17 - 20 ]. In CRC, the sensitivity and specificity of this approach reportedly ranges from 90 - 95% [ 14 , 17 , 19 , 21 - 24 ]. Importantly, analysis of the diagnostic 'peptidome' of patients' blood serum is amenable to repeated sampling and might potentially be used to monitor disease course following surgery with the aim of predicting disease recurrence.…”
Section: Introductionmentioning
confidence: 99%